HUBUNGAN KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK TERHADAP PEMBELAJARAN MATEMATIKA PADA POKOK BAHASAN HIMPUNAN DI MTs RAUDHATUL AKMAL - Feby Pratiwi; Mahyu Lida; Syarifah Widya Ulfa (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research examines the Mathematical Problem Solving Ability of Students Against Mathematics Learning in the Subject of the Association. The research was conducted at Mts Raudhatul Akmal in the odd semester, namely in 2022/2023. The population used for this research was MTs students who were in class VII as many as 80 students. The research was carried out in the form of giving questions that were distributed by the teacher to each student in the form of a test of students' mathematical problem solving abilities. Data analysis used prerequisite test of linear regression model, correlation coefficient test of Pearson/Product Moment formula, correlation coefficient t test, and coefficient of determination. The results of this study indicate that there is a significant relationship between mathematical problem solving abilities and students' mathematical communication abilities as a whole. That is, the higher the mathematical problem solving ability, the higher the student's mathematical communication ability. On the contrary, at the high, medium, and low ability levels, the relationship that occurs is a negative relationship. meaning that the higher the mathematical problem solving ability, the lower the mathematical communication ability.